Essential Oil Composition, Antioxidant and Antifungal Activities of Salvia sclarea L. from Munzur Valley in Tunceli, Turkey - Yuce, E.; Yildirim, N.; Yildirim, N. C.; Paksoy, M. Y.; Bagci, E. (C M B Assoc, 2014)
The essential oil composition and in vitro antioxidant and antifungal activity of the Salvia sclarea L. from Munzur Valley in Tunceli, Turkey were evaluated in this research. The in vitro antifungal activity of ethanol, hexane and aqueous extracts of S. sclarea against pathogen fungi Epicoccum nigrum and Colletotrichum coc-codes were investigated. The essential oil of aerial parts of S. sclarea was obtained by hydrodistillation and was analysed by GC and GC-MS. Total antioxidant status was determined by using Rel assay diagnostics TAS assay kit (Lot. RL024) by Multiscan FC (Thermo). 33 compounds were identified representing the 85.0% of the total oil. The most abundant components (> 5%) of the S. sclarea essential oils were caryophyllene oxide (24.1%), sclareol (11.5%), spathulenol (11.4%), 1H-naphtho (2,1,6) pyran (8.6%) and beta-caryophyllene (5.1%). The best antifungal and antioxidant effect was seen in ethanolic S. sclarea extract. It can be said that Salvia sclerae could be used as natural antioxidant.
Keywords: Salvia sclarea; Essential oil; Antioxidant activity; Antifungal activity